2011
DOI: 10.1016/j.ajpath.2011.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Cysteinyl Leukotriene 2 Receptor in Novel Expression Sites of the Gastrointestinal Tract

Abstract: Cysteinyl leukotrienes (cysLTs: LTC₄, LTD₄, and LTE₄) are pro-inflammatory lipid molecules synthesized from arachidonic acid. They exert their actions on at least two cysLT receptors (CysLT₁R and CysLT₂R). Endothelial expression and activation of these receptors is linked to vasoactive responses and to the promotion of vascular permeability. Here we track the expression pattern of CysLT₂R in a loss-of-function murine model (CysLT₂R-LacZ) to neurons of the myenteric and submucosal plexus in the small intestine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Using a loss‐of‐function murine model (CysLT 2 R‐LacZ), CysLT 2 receptor expression has been identified in neurons of the myenteric and submucosal plexus in the small intestine, colonic myenteric plexus, dorsal root ganglia and inferior ganglion of the vagal nerve (Barajas‐Espinosa et al ., ). In this model, LTC 4 /D 4 stimulation of colonic submucosal venules elicited a reduced permeability response in CysLT 2 receptor knockout (CysLT 2 −/− ) mice compared with WT mice, while basal neuronal activity of colonic‐projecting nociceptive neurons from dorsal root ganglia showed significantly higher excitability.…”
Section: Cyslt Receptorsmentioning
confidence: 97%
“…Using a loss‐of‐function murine model (CysLT 2 R‐LacZ), CysLT 2 receptor expression has been identified in neurons of the myenteric and submucosal plexus in the small intestine, colonic myenteric plexus, dorsal root ganglia and inferior ganglion of the vagal nerve (Barajas‐Espinosa et al ., ). In this model, LTC 4 /D 4 stimulation of colonic submucosal venules elicited a reduced permeability response in CysLT 2 receptor knockout (CysLT 2 −/− ) mice compared with WT mice, while basal neuronal activity of colonic‐projecting nociceptive neurons from dorsal root ganglia showed significantly higher excitability.…”
Section: Cyslt Receptorsmentioning
confidence: 97%
“…Previous work by our laboratory demonstrated that activation of vascular CysLT 2 R in cremaster muscle venules leads to an exudation of fluorescein isothiocyanate (FITC)‐labeled albumin via a transcellular vesicle transport mechanism (8). As well, we have recently found that CysLT 2 R activation partially mediates vascular permeability following exogenous addition of cysLTs or inflammation in the colon that expresses CysLT 2 R in nonvascular niches (9). In this study, we identify the retinal vasculature as an expression site of CysLT 2 R and elucidate its involvement in retinal pathophysiology.…”
mentioning
confidence: 93%
“…CysLT 2 R has not received as much attention as CysLT 1 R, although there has been a wave of interest concerning this receptor in cardiovascular disease (Funk, 2005). CysLT 2 R is expressed in multiple organs in the mouse, including the heart (Jiang et al, 2008), brain, cremaster muscle vasculature , and myenteric neurons (Barajas-Espinosa et al, 2011). In humans, it is found in umbilical cord endothelial cells (Lötzer et al, 2003;Uzonyi et al, 2006), myocardium, and coronary vessels (Kamohara et al, 2001).…”
Section: Introductionmentioning
confidence: 99%